Retarding oxidation of copper nanoparticles without electrical isolation and the size dependence of work function. Issue 1 (December 2017) - Dabera, G. Dinesha M.R.; Walker, Marc; Sanchez, Ana; Pereira, H. Jessica; Beanland, Richard; Hatton, Ross
Abstract Copper nanoparticles (CuNPs) are attractive as a low-cost alternative to their gold and silver analogues for numerous applications, although their potential has hardly been explored due to their higher susceptibility to oxidation in air. Here we show the unexpected findings of an investigation into the correlation between the air-stability of CuNPs and the structure of the thiolate capping ligand; of the eight different ligands screened, those with the shortest alkyl chain, –(CH2 )2 –, and a hydrophilic carboxylic acid end group are found to be the most effective at retarding oxidation in air. We also show that CuNPs are not etched by thiol solutions as previously reported, and address the important fundamental question of how the work function of small supported metal particles scales with particle size. Together these findings set the stage for greater utility of CuNPs for emerging electronic applications. Copper nanoparticles are susceptible to oxidation in air, which limits their applications. Here, the authors reveal correlations between the stability of a Cu nanoparticle and the structure of its passivating ligand, finding that short chain thiols are surprisingly more effective at retarding oxidation than longer chain ones.